A study on students’ anxiety level and self-confidence towards speaking English as a second language: a case of law students / Zulaikha Khairuddin - Khairuddin, Zulaikha (2015)
Speaking skill is one of the most challenging skills among the four English skills which are listening, speaking, reading and writing respectively. Hence, it is important for students to speak in English confidently and they can use speaking strategies in order to avoid anxiousness. The main purpose of this study was to investigate the association between two variables which are level of speaking anxiety and level of self-confidence. The other objectives that this study would like to explore are to identify level of speaking anxiety among Law students, to identify level of confidence when speaking among Law students, to determine if there is any significant difference in level of speaking anxiety and level of confidence when speaking among Law students based on their demographic details (gender, university, ethnicity, MUET result, year of study, first language) respectively. This study employed a purely quantitative study and correlational design was selected as the research design. The instrument used in this study was questionnaire.There were 380 respondents participated in this study which were Law students from four public universities in Malaysia. The result from this study indicated that Law students’ level of speaking anxiety in English was moderate while the level of self-confidence among Law students was above average. The study also showed that there was a significant difference based on the universities that Law students come from and their first language in terms of level of speaking anxiety in English. It is also portrayed that there was a significant difference in terms of Law students’ level of self-confidence based on their MUET result and first language correspondingly. Next, the study revealed that there was a weak significant association between level of speaking anxiety in English and were students, lecturers, the Faculty of Law, the universities and the policy maker to discuss and develop solutions for this issue. Hence, mastering to speak English for ESL learners is important.